III-V semiconductor nanowire for solid oxide fuel cells - Muhammad, R. (2015)
Solid oxide fuel cells (SOFC) have much promise as efficient devices for the direct conversion of the energy stored in chemical fuels into electricity. The development of highly robust SOFC that can operate on a range of fuels, however, requires improvement in the electrodes, especially the anode, where nanoscale engineering of the structure is required in order to maximize the number of sites where the electrochemical reactions take place. In this article, we briefly explained the growth of III-V semiconductor nanowire layer on GaAs substrate as an anode electrodes using metal organic chemical organic vapor deposition (MOCVD). Field-emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM) and conductivity atomic force microscopy (CAFM) analysis were carried out to investigate the structural properties and current-voltage changes in the wires. Results show that the III-V nanowires grow with less defect structure, uniform in composition and diameters with optimal growth parameters. The current-voltage measurement showed similar to that of a p-n junction characteristic which is suitable in the SOFC application.